An Analysis of Teacher Resilience at Waladun Shalih Ratulangi Kindergarten in Palopo City - Asmi, Ulul; Yusuf, Munir; Subhan, Subhan (Universitas Negeri Makassar, 2024)
This study examines teacher resilience at Waladun Shalih Ratulangi Kindergarten in Palopo City, focusing on the challenges faced by early childhood educators. Using a descriptive qualitative approach, the research employs data collection techniques such as observation, interviews, and documentation. Data analysis follows the steps of reduction, presentation, and conclusion drawing. The findings reveal that (1) Teacher resilience aligned with the CO2RE dimensions: Control, Origin, Reach, and Endurance.; (2) Factors influencing resilience include intrinsic motivation and teacher creativity, which drive problem-solving and adaptability; and (3) Efforts to enhance resilience encompass transforming failures into opportunities, accepting constructive criticism, fostering courage and persistence, and expanding social networks. The study contributes insights into strategies for sustaining teacher resilience in early childhood education, highlighting its significance in overcoming professional and personal challenges. The results provide actionable recommendations for educators, administrators, and policymakers to support resilience development in educational settings.